Protocol Converter for Serial Communication Between Digital Rectifier Controllers and а Power Plant SCADA System - Vukic, Vladimir (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
The paper describes the protocol converter INT-485-MBRTU, developed for serial communication between the thyristor rectifier (based on the proprietary protocol “INT-CPD-05”, according to standard RS-485) and the SCADA system (based on protocol “Modbus RTU”, of the same standard) in the thermal power plant “Nikola Tesla B1”. Elementary data on industrial communication protocols and communication gateways were provided. The basic technical characteristics of the “Omron” programmable logic controller CJ series were described, as well as the developed device INT-485-MBRTU. Protocol converters with two versions of communication software were tested, differing only in one control word, intended for a forced successive change of communication sequences, in opposite to automatic sequence relieve. The device INT-485-MBRTU, with the program for forced successive change of communication sequences, demonstrated the reliability of data transfer of 100 %, in a sample of approximately 480 messages. For nearly the same sample, the same protocol converter, with a version of the program without any type of message identifiers, transferred less than 60 % of the foreseen data. During multiple sixty-hour tests, the reliability of data transfer of at least 99.9979 % was recorded, in 100 % of the analyzed cases, and for a sample of nearly 96,000 pairs of the send and receive messages. We analyzed the results and estimated the additional possibilities for application of the INT-485-MBRTU protocol converter.